Growth impact of CO2 emissions caused by tourist arrivals in Turkey An econometric approach - Yorucu, Vedat (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this study is to analyze the determinants of changes in carbon dioxide (CO2) emissions for Turkey by utilizing the autoregressive distributed lag approach to investigate the long-run equilibrium relationships of CO2 emissions between foreign tourist arrivals (FTAs) and electricity consumption (ELC). The results reveal that foreign tourists and ELC are significant determinants of a long-run equilibrium relationship with CO2 emissions from electricity and heat production and CO2 emissions from transport for Turkey, respectively. The results of the conditional error correction models (CECM) confirm that there are long-run causal relationships from the growing number of foreign tourist arrivals and the increase of ELC toward the growth of CO2 emissions during 1960-2010. The results of autoregressive distributed lag (ARDL) error correction models for CO2 emissions also validate significant dynamic relationships between CO2 emissions, ELC and tourist arrivals in the short run. Design/methodology/approach - ARDL modeling and Bounds test approach were used in this study. Findings - Rapid tourism development in Turkey has triggered CO2 emissions. The growth of CO2 emissions in Turkey threatens sustainability. The hypothesis of The growth of CO2 emissions in Turkey is validated. Tourist arrivals, ELC and CO2 emissions are co-integrated. CECMs confirm the growth of CO2 emissions during 1960-2010. ARDL modeling shows significant relationships between CO2 emissions and other variables. Originality/value - Results of ARDL error correction models for CO2 emissions validate the hypothesis that there are significant dynamic relationships between CO2 emissions, ELC and tourist arrivals in Turkey for the short run.
Keywords: Turkey; ARDL-Bounds test; CO2 emissions; Conditional causality; Electricity consumption; Tourist arrivals